Titanium carbide MXene: Synthesis, electrical and optical properties and their applications in sensors and energy storage devices - Michael, Johnson; Qifeng, Zhang; Danling, Wang (Nanomaterials and nanotechnology, 2019)
MXenes have been under a lot of scientific investigation due to the novel characteristics that are inherent to two-dimensional nanostructures. There are a multitude of MXenes being studied and one of the most popular among these would be the titanium carbides. The general formula for titanium carbide is Ti n + 1C n for the nanosheets produced that have undergone much study in the past few years. These studies include how the etching process affects the final MXene sheet and how the post-processing via heat or combining with polymers and/or inorganic compounds influences the mechanical and electrical properties. It is found that different etching techniques can be used to change the electrical properties of the produced MXenes and different post-processing techniques can be used to further change the properties of the nanosheets. The possible application of the titanium carbide MXenes as chemical sensing and energy storage materials will be briefly discussed. MXene nanosheets show promise in such devices due to their high surface area to volume ratio and their specific surface structure with feasible surface functionalization.